MDC e MMC: uma ênfase a partir de um processo de ensino e aprendizagem contextualizado - PRAXEDES, Luiz Eduardo (2022)
The present work aims to develop a study of the (Maximum Common Divisor) MDC and (Least Common Multiple) MMC emphasizing it from a contextualized teaching/learning process. At first, the historical context, definitions of MDC and MMC and the relationship between them are presented, which will serve as prerequisites for the development of the theme. The relevance of the research focuses on applications with problems related to everyday life to show that they can be used in practical situations, especially in questions that relate theoretical knowledge to contextualized problems. Aiming at this aspect, a teaching methodology is developed in which it is possible to offer the student a knowledge that takes into account the significant learning of the proposed theme. Therefore, it is clear that teaching, being dynamic and motivating, provides greater curiosity and interest in the content, considering that in order to value learning it is necessary that the teacher knows how to build a teaching process that does not fit only in a technical method. which can cause learning difficulties. The research concludes considering that the study of MDC and MMC when applied in contextualized problem situations can offer a better understanding for students when considering the learning of everyday life.